Study of A.C Electrical Properties of Aluminum–Epoxy Composites - Jafar, H I; Ali, N A; Shawky, A (Al-Nahrain Journal of Science, 2018)
This work studies the electrical properties for pure epoxy (EP), and epoxy with (20%,30%,40% and 50%)aluminum powder composites. The electrical conductivity [σ(w)a.c] for these materials have been measured over the frequency range (102 -106)Hz at room temperature. It is found the A.C conductivity increased when increased the concentration of aluminum. It is found for all samples, the curves for real part of dielectric constant (ε) and dissipation factor (tanδ). The dielectric constant increased smoothly with an increase in the concentration of aluminum it was attributed to interfacial polarization and decrease with increased frequency. In general, dissipation factor values for composites with higher concentrations of aluminum were greater than those with lower volume content of aluminum. Also, the dissipation factor showed an increase with a decrease in frequency. It was found that a.c electrical conductivity increases with increasing frequency according to the relation s(w)=Aws has been observed , with values of exponent (s) less than unity for all samples and decrease with the increase of frequency and lie between (0.3 to 0.6) unit . Also, it was found that the correlated barrier hopping (CBH) is the dominant conduction mechanism.